PENGARUH KOMPENSASI, KOMUNIKASI, KOMPETENSI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA BADAN PENGELOLA KEUANGAN DAN ASET DAERAH (BPKAD) KABUPATEN LABUHANBATU - Hasibuan, Muhammad Ridho Rahmansyah; Lubis, Junita; Hutagaol, Anita Sri Rejeki (Jurnal Investasi, 2025)
The Regional Financial and Asset Management Agency (BPKAD) of Labuhanbatu Regency is the subject of this study, which aims to examine the relationship between employee performance and factors including salary, communication, competence, and work discipline. Increasing employee effectiveness in managing regional funds and assets to support good governance is the main topic underlying this study. Using a saturated sample technique, researchers in this study surveyed 44 BPKAD employees of Labuhanbatu Regency to compile quantitative data. The data were analyzed using multiple linear regression analysis after conducting conventional assumption tests. At a level greater than the t-table, this study found that the remuneration variable had a positive and statistically significant effect on employee performance. Other characteristics that had a significant and positive effect on employee performance were competence, communication, and work discipline. The four independent determinants at BPKAD Labuhanbatu Regency simultaneously had a significant effect on employee performance, which was 76% of the performance difference and the remaining 24% was influenced by other variables not studied. These results have real consequences for the executives of BPKAD Labuhanbatu Regency, who should prioritize aspects such as remuneration, communication, competence, and work discipline if they want to see better performance from their employees